Treatment of multiple diastemas in maxillary anterior teeth with indirect veneers: A case report - Juniarti, Devi Eka; Aji Prasidha, Satria; Zada Aramita Putri, Rhegina; Kartini Sunur, Yulianti (Universitas Airlangga, 2022)
Background: Multiple diastema is one of the most frequently encountered aesthetic problems related to patient confidence. This problem is still a challenge for the clinician to restore the gap between the teeth as desired by the patient. Indirect veneers have been approved as one of the treatment plans to deal with this aesthetic problem. Purpose: This case report aims to describe the management of multiple diastema in maxillary anterior teeth with indirect veneer restorations. Case: A 20-year-old woman came to RSKGM Universitas Airlangga with the main complaint of a gap between her upper front teeth. The patient was then explained about all the treatment options and agreed to a treatment plan for the indirect veneers restoration. Case Management: Treatment was carried out in 5 visits involving 6 maxillary anterior teeth. The teeth were vital and there was no discoloration. Post-treatment control was carried out one week after insertion. One of the advantages of bonded porcelain veneers is the minimally invasive treatment. Only 0.5 mm reduction was required on the incisal and labial surfaces. Conclusion: Indirect veneer restoration with minimally invasive techniques can provide good results in treating multiple diastema in the maxilla.